Internal communication and employee performance: The mediating role of motivation - Maria Yulita Dhone; Endi Sarwoko (Jurnal Ekonomi Modernisasi, 2022)
Internal communication is an important function in an organization in relation to human resource management. This research examined the employee-perceived internal communication and investigated the role of internal communication and employee motivation on employee performance. The mediating influence of motivation in influence of internal communication on organizational performance was also investigated. Questionnaires were distributed to employees of BPJS Malang City to collect the data of this study. Path Analysis was performed to analyze the data, which results revealed that internal communication could improve employee performance. Internal communication was also found to enhance employee motivation, which in turn would affect the employee performance. Internal communication will encourage organization-employee relationship. Employees should understand the company's core business to make them aware of the targets to achieve. Through effective internal communication, employees would have better comprehension on the importance of their performance. Future researchers are encouraged to examine job satisfaction as a mediating variable in the relationship between internal communication and employee performance